Diuretiki - Kržan, Mojca (Medicinski razgledi, 2005)
This article describes drugs influencing water and electrolyte excretion, called diuretics. Most of them modify the transport of sodium ions in tubular epithelial cells via different mechanisms. They are the drug of choice for thetreatment of hypertension and diseases with concomitant edema, such as congestive heart failure, electrolyte disturbances, kidney diseases and liver cirrhosis.
Keywords: Diuretiki; Diuretics; Diuretiki ozmotski; Pharmacology; Diuretiki tiazidni; Carbonic Anhydrase Inhibitors; Ogljikova anhidraza, inhibitorji; Diuretics, Osmotic; Diuretics, Thiazide; Spironolakton; Spironolactone; farmakologija